Reflections on the Challenges Facing Public Interest Lawyers in Post-Apartheid South Africa - Asha Ramgobin (Washington University Journal of Law & Policy, 2001)
This Article, through the use of case studies and reflections, will conclude that finding the “Middle Way” has become the singular challenge facing teachers, students, and practitioners of public interest law.
Keywords: Legal assistance to the poor – South Africa; Land titles – South Africa; Pardon – South Africa; Pro bono legal services; Land tenure; Low income housing